2003
DOI: 10.1046/j.1439-0434.2003.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotics on the Symptoms of Stunting Disease of Magnolia liliiflora Plants

Abstract: Treatment of diseased magnolia plants with Oxytetracycline, Baytril or Tylan did not reduce the number of symptomatic plants, but promoted shoot growth, development of symptomless leaves and flower buds. The most efficient were 500 ppm Baytril, 200 ppm Tylan and 500 or 1000 ppm Oxytetracycline. Lower concentrations of Baytril and Oxytetracycline were less effective and higher concentrations of Tylan decreased the growth of magnolia shoots. All the tested antibiotic treated and untreated magnolias were shown by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…1968; Freitag and Smith 1969; Andersen et al. 2001; Kamińska and Śliwa 2003; Wongkaew and Fletcher 2004), but symptoms in treated plants mostly reappeared after the transfer of plants to antibiotic‐free medium. Bradel et al.…”
Section: Introductionmentioning
confidence: 99%
“…1968; Freitag and Smith 1969; Andersen et al. 2001; Kamińska and Śliwa 2003; Wongkaew and Fletcher 2004), but symptoms in treated plants mostly reappeared after the transfer of plants to antibiotic‐free medium. Bradel et al.…”
Section: Introductionmentioning
confidence: 99%
“…Till today, all the treatments against phytoplasmas have proved ineffective. Tetracyclines are known to have a bacteriostatic effect on phytoplasmas (Davis et al , 1968; Freitag & Smith, 1969; Šarić & Cvjetković, 1985; Bradel et al , 2000; Andersen et al , 2001; Kamińska & Śliwa, 2003). However, symptoms in treated plants would reappear after prolonged growth without the antibiotic, and phytoplasma presence was confirmed by PCR assays.…”
Section: Introductionmentioning
confidence: 99%
“…RFLP profiles indicated that detected phytoplasmas belonged to the 16SrI group – subgroup B, now re‐classified as the species ‘ Candidatus Phytoplasma asteris’, and to the 16SrX group – subgroup A, now re‐classified as the species ‘ Candidatus Phytoplasma mali’. In Poland, 16SrI‐B subgroup strains affect several ornamental crops including magnolia, rose, lily, tulip, freesia, and bleeding heart, while the 16SrX‐A subgroup strain has been recorded less frequently, only in magnolia and rose (Kamińska & Śliwa, 2003, 2004). This report confirms infection of dahlia by aster yellows phytoplasma belonging to group 16Sr‐B, and records for the first time, infection by phytoplasma of group 16SrX‐A.…”
mentioning
confidence: 99%